Mediating effects of stigma on the relationship between contact and willingness to care for people with mental illness among nursing students. (August 2021) - Gu, Libin; Xu, Deguo; Yu, Mingming
Abstract: Background: Previous studies have demonstrated that contact positively impacts nursing students' willingness to care for people with mental illness. However, studies that have explored the mechanism of such a relationship between contact and willingness remain few. Objectives: To examine the direct relationship between contact and nursing students' willingness to care for people with mental illness and to explore the potential mediating roles of stigma. Design: This was a cross-sectional study design. Settings: The study was conducted in a nursing school in Nanjing city, China. Participants: A total of 839 nursing students were recruited in the study through convenience sampling. Methods: Nursing students' stigma, contact, and willingness to care for people with mental illness were measured online through the Stigma toward People with Mental Illness Scale (SPMI), the Level of Contact Report, and one item of "which degree indicates your willingness to provide care for people with mental illness, " respectively. The structural equation model was applied to explore the potential mediating roles of stigma. Results: Contact with people suffering from mental illness directly affected nursing students' willingness to care for them ( β = 0.076, p < 0.05). Meanwhile, stigma partly mediated the effect of students' contact on willingness to care for people with mental illness ( β = 0.048, p < 0.05). Conclusions: High level of contact can improve nursing students' willingness to care and the relationship is partly mediated by stigma. Measures to improve the level of contact and reduce stigmatizing attitudes of nursing students are accordingly essential in influencing them to have more willingness to care for people with mental illness. Highlights: Nursing students' willingness to care for people with mental illness is at a medium level. Contact has a positive effect on willingness to care directly and indirectly via stigma. Measures to improve contact level and reduce stigma are essential for willingness improvement.